TMEM Proteins in Cancer: A Review - Schmit, Kathleen; Michiels, Carine (Frontiers in Pharmacology, 2018)
A transmembrane protein is a type of protein that spans biological membranes. Many of them extend through the lipid bilayer of the plasma membrane but others are located to the membrane of organelles. The transmembrane protein (TMEM) family gathers proteins of mostly unknown functions. Many studies showed that TMEM expression can be down- or up-regulated in tumor tissues compared to adjacent healthy tissues. Indeed, some TMEMs such as TMEM48 or TMEM97 are defined as potential prognostic biomarkers for lung cancer. Furthermore, experimental evidence suggests that TMEM proteins can be described as tumor suppressors or oncogenes. TMEMs, such as TMEM45A and TMEM205, have also been implicated in tumor progression and invasion but also in chemoresistance. Thus, a better characterization of these proteins could help to better understand their implication in cancer and to allow the development of improved therapy strategies in the future. This review gives an overview of the implication of TMEM proteins in cancer.